2021
DOI: 10.4028/www.scientific.net/amr.1164.87
|View full text |Cite
|
Sign up to set email alerts
|

Development of Green Cementitious Materials by Using the Abrasive Waterjet Garnet Wastes: Preliminary Studies

Abstract: The constant need for recycling, waste prevention and general environmental protection represent the new directive approaches imposed by the geo-political, industrial and environmental context, at the regional, European and global level. Ensuring the environmental protection and reducing the natural resources consumption represent general purposes of the sustainable development and also considerations to implement the Circular Economy Model [1]. The present study is developed with respect to the previously men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…AWJ material processing represents a relatively new and extremely efficient method in the specific industries, implying various applicability areas, attributed to different materials, with different properties and domains of use, Figure 2. The material processing, besides cutting includes drilling, milling, sandblasting and cleaning as well, as the versatility of the technique and the associated research for continuous improvement determines its large applicability in many complementary or distinct fields [13][14][15][16]. The use of waterjets is not new: the Egyptians used it also combined with sand for mining and cleaning purposes; when the technology allowed the increase of water pressure, the technique was adapted for forestry activities, as well.…”
Section: Abrasive Waterjet (Awj) Methods For Materials Industrial Pro...mentioning
confidence: 99%
“…AWJ material processing represents a relatively new and extremely efficient method in the specific industries, implying various applicability areas, attributed to different materials, with different properties and domains of use, Figure 2. The material processing, besides cutting includes drilling, milling, sandblasting and cleaning as well, as the versatility of the technique and the associated research for continuous improvement determines its large applicability in many complementary or distinct fields [13][14][15][16]. The use of waterjets is not new: the Egyptians used it also combined with sand for mining and cleaning purposes; when the technology allowed the increase of water pressure, the technique was adapted for forestry activities, as well.…”
Section: Abrasive Waterjet (Awj) Methods For Materials Industrial Pro...mentioning
confidence: 99%
“…Considering their ability to generate steady abrasive flows, with no blockages occurring in the focusing tubes, Garnets can be successfully used to gain edge cutting accuracy as complementary waterjet cutting operations for diverse materials stone, granite and marble cutting, metalworking (Carbon and Stainless Steel, Aluminum, Copper), ceramic and glass, FRP and Carbon fibre, plastic and timber cutting etc.) [9,17,18]. According to last decade data, worldwide, there are four dominant Garnet producing countries: India (700 000 metric tonnes), China (470 000 metric tonnes), Australia (150 000 metric tonnes), and the United States (54 000 metric tonnes) [16,19].…”
Section: Abrasive Garnet Sands For Industrial Application and The Der...mentioning
confidence: 99%
“…Recently, the studies performed in the topic of valorising Garnet-type wastes in mortars and concrete increased, proving the growing interest of academia and also the industry, on both directions: the alkali activated materials and also the cement-based ones. The initial studies available till 2019 were quite scarce and offered a preliminary preview regarding the potential of Garnet wastes as a partial substitute of the aggregate (fillers) in concrete [9]. Recent studies confirmed this potential and validated some of initially launched assumptions, offering complementary information and guiding lines for further investigation.…”
Section: Introductionmentioning
confidence: 98%
“…Such an analysis helps civil engineers in optimizing the process of structural intervention by deepening the understanding of how the building works from the structural point of view and also considering the concrete mix design and the associated physical, mechanical, and durability characteristics. Therefore, the interventions can be targeted on those elements that have a deficient behavior, which can induce negative effects into the structure [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The viability of the method should also be verified on various types of concrete mix design developed with different additions, waste, or by-products (mineral, rubber, plastic, glass, etc. ), which gained large diversity in recent years due to www.videleaf.com environmental protection requirements and Circular Economy implementation [2][3][4].…”
Section: Introductionmentioning
confidence: 99%